Evaluating warm-up strategies for elite sprint breaststroke swimming performance - McGowan, C. J.; Pyne, D. B.; Thompson, K. G.; Rattray, B. (International Journal of Sports Physiology and Performance, 2016)
Purpose: Targeted passive heating and completion of dryland-based activation exercises within the warm-up can enhance sprint freestyle performance. The authors investigated if these interventions would also elicit improvements in sprint breaststroke swimming performance. Methods: Ten national and internationally competitive swimmers (~805 FINA (Fédération internationale de natation) 2014 scoring points; 6 men, mean ± SD 20 ± 1 y; 4 women, 21 ± 3 y) completed a standardized pool warm-up (1550 m) followed by a 30-min transition phase and a 100-m breaststroke time trial. In the transition phase, swimmers wore a conventional tracksuit and remained seated (control) or wore tracksuit pants with integrated heating elements and performed a 5-min dryland-based exercise routine (combo) in a crossover design. Results: Performance in the 100-m time trial (control: 68.6 ± 4.0 s, combo: 68.4 ± 3.9 s, P = .55) and start times to 15 m (control: 7.3 ± 0.6 s; combo: 7.3 ± 0.6 s; P = .81) were not different between conditions. It was unclear (P = .36) whether combo (-0.12°C ± 0.19°C [mean ± 90% confidence limits]) elicited an improvement in core temperature maintenance in the transition phase compared with control (-0.31°C ± 0.19°C). Skin temperature immediately before commencement of the time trial was higher (by ~1°C, P = .01) within combo (30.13°C ± 0.88°C [mean ± SD]) compared with control (29.11°C ± 1.20°C). Lower-body power output was not different between conditions before the time trial. Conclusions: Targeted passive heating and completion of dryland-based activation exercises in the transition phase does not enhance sprint breaststroke performance despite eliciting elevated skin temperature immediately before time trial commencement.